IMPLEMENTASI PENDIDIKAN PESANTREN KOPI DALAM MEMBENTUK JIWA ENTRERPRENEUR SANTRI - Sauri, Sofyan; Fawaidi, Badrun (International Conference on Humanity Education and Society (ICHES), 2024)
This research aims to describe the implementation of coffee boarding school education in forming the entrepreneurial spirit of students at the At-Tanwir Islamic Boarding School. Therefore, this research uses a qualitative method with a case study type of research. The results of this research show that the At-Tanwir Islamic Boarding School has implemented the Coffee Islamic Boarding School Education in forming the entrepreneurial spirit of students. This coffee boarding school education is applied to students who have graduated from vocational high schools (SMK). This coffee boarding school education can change their mindset so that they no longer choose to work overseas, but they can develop the talents they have gained in this coffee boarding school education to become entrepreneurs. This education is carried out twice a week, namely on Sundays and Thursdays.